2020
DOI: 10.1186/s13059-020-1942-6
|View full text |Cite
|
Sign up to set email alerts
|

A framework for transcriptome-wide association studies in breast cancer in diverse study populations

Abstract: Background: The relationship between germline genetic variation and breast cancer survival is largely unknown, especially in understudied minority populations who often have poorer survival. Genome-wide association studies (GWAS) have interrogated breast cancer survival but often are underpowered due to subtype heterogeneity and clinical covariates and detect loci in non-coding regions that are difficult to interpret. Transcriptome-wide association studies (TWAS) show increased power in detecting functionally … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 100 publications
2
68
0
Order By: Relevance
“…A framework for transcriptome-wide association studies in breast cancer in diverse study populations [45] The median CV R 2 for the 153 genes is 0.011 in both African American and white women.…”
Section: Title Of the Publication Description Of Prediction Accuracymentioning
confidence: 99%
“…A framework for transcriptome-wide association studies in breast cancer in diverse study populations [45] The median CV R 2 for the 153 genes is 0.011 in both African American and white women.…”
Section: Title Of the Publication Description Of Prediction Accuracymentioning
confidence: 99%
“…Subsequently, we explored whether we could identify ancestry-specific enriched oncogenic pathways with prognostic relevance in BasalMyo tumors. In support of this concept, a recent transcriptome-wide association study of the Caroline Breast Cancer Study transcriptomic dataset, comprising of selfidentified African-American and European-American women, demonstrated that ancestry-stratified predictive risk models did not perform across ancestries and/or subtype 65 . Through integrative analysis of differential enrichment and prognostic connotation, we identified seven differentially enriched signaling pathways with prognostic connotation in patients of EA and/or AA.…”
Section: Discussionmentioning
confidence: 99%
“…Expression weights from the model with the largest R 2 were used to compute TWAS association statistics. More details can be found in the original manuscript 18 and other publication 52 .…”
Section: Methodsmentioning
confidence: 99%